Application of ELECTRE and TOPSIS methods in selecting synthetic lubricating oil suppliers to minimize delays in aircraft maintenance activities - Zabidi, Yasrin; Rengganis, Esa; Harliyus A, S, Harliyus; R, Fajar Khanif (Institute of Computer Science (IOCS), 2025)
One of the obstacles often faced when carrying out aircraft maintenance activities is the unavailability of lubricating oil that meets the established quality standards due to delays in the supply of lubricating oil from suppliers. In order for maintenance activities to be carried out according to the specified schedule, continuous availability of lubricating oil from suppliers is needed. Therefore, it is necessary to conduct research on the selection of reliable or trustworthy lubricating oil suppliers in supplying lubricating oil needs that meet the established quality standards. In selecting a lubricating oil supplier, the ELECTRE and TOPSIS methods are combined, where the ELECTRE method is used to process the weight of each supplier criterion and the TOPSIS method is used to rank alternative solutions obtained from the ELECTRE method classification.It is hoped that by combining these methods, recommendations for reliable suppliers can be provided. The suppliers selected as partners for providing lubricating oil are supplier C with an A* value of 3.090 and supplier B with an A* value of 2.973. The selection of suppliers is based on supplier performance with 6 criteria, namely the quality of lubricating oil, the price of lubricating oil, the responsiveness of the supplier's service and response, the speed of delivery to partner expeditions and the policy of replacing damaged or leaking lubricating oil